Pengaruh Promosi dan Akreditasi Terhadap Minat Mahasiswa Baru - Abu Bakar; Dicky Jhon Anderson Butarbutar; Asni Hasanudin; Nurul Mukhlishah; Devi Sakianah (LPPM Institut Pesantren KH. Abdul Chalim, 2022)
In order to face competition and maintain the existence of universities, it is necessary to have a good marketing strategy. In attracting new students, several important factors are influenced, including promotion and good college accreditation. This study aims to analyze the effect of promotion and accreditation either partially or jointly. The independent variables in this study were promotion (X1) and accreditation (X2), while the interest of new students (Y) became the dependent variable or was measured in this study. The method used is a quantitative method and a survey approach, the data used are primary data, the method of obtaining data is by distributing questionnaires to respondents and the instrument used is using a Likert scale 1-5 which has been tested for validity and reliability tests. Data processing and analysis in this study used SPSS 25. The results showed that partially promotion had a significant effect on new student interest, while accreditation also had the same impact, while simultaneously promotion and accreditation had a significant effect.